ANALISIS TINGKAT PENCEMARAN LINGKUNGAN PADA KOTA/KABUPATEN DI JAWA TENGAH MENGGUNAKAN METODE K-MEANS - resnu maulana (Universitas Lampung, 2023)
Abstract. Mining activities can cause environmental pollution, as happened in the villages of Wadas and Kendeng, Central Java. The aim of this research is to classify the level of environmental pollution in Central Java based on a number of parameters, namely, the number of villages affected by water pollution, air pollution and soil pollution. The clustering method in this study uses the K-Means algorithm. The best cluster is 0.51 with 2 clusters. Based on the level of environmental pollution, the findings reveal that Central Java is divided into two city/district clusters: cluster 1 (with a low pollution level) with 14 members, and cluster 2 (with a low pollution level) with 24 members.